Short stay management of acute heart failure - Peacock, W. Frank (Contemporary Cardiology, 2012)
This timely book is a road map for defining the care of acute heart failure patients in the short stay or observation unit setting. Produced in collaboration with the Society of Chest Pain Centers, this book provides an understanding of the diverse medical needs and solutions, administrative processes, and regulatory issues necessary for successful management. In an environment of increasing financial consciousness, medical practice is changing drastically. Short stay care is premier among the new specialties that cater to the complex balance of optimizing patient outcomes while minimizing fiscal burdens. The observation unit has proven to be an excellent arena for the care of acute heart failure, replete with opportunities to improve both medical management and quality metrics. Unique to the field, Short Stay Management of Acute Heart Failure, Second Edition is the only book of its kind, providing the medical, regulatory, and economic tools necessary to create and implement successful short stay management protocols and units for the care of the heart failure patient. It is an essential guide for health care professionals and for hospitals and institutions wishing to be recognized as quality heart failure centers as accredited by the Society of Chest Pain Centers.